Absorção acústica na qualidade do ambiente construído: da sala de estar ao estúdio de som - Rosa, Lourdes Zunino (1992)
The matter of this work is to introduce an instrument assisting to the resolution of certain acoustical question, current in architecture as, for instance, the ambient reverberation. It consists in the approach of basic concepts in architectonic acoustics as well as, tecnical files of the acoustic absorption performance of certain materials, which can be found in the brasilian market. The material performance analyses is presented through comparative graphic. Necessities of the market were checked.